RETRACTED: Dynamics of desertification of arid ecosystems of Kizlyar pastures - Ashurbekova Tamila; Magomedova Diana; Omarieva Luisa; Gadzhimusayeva Zaira; Krotova Olga (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001